DENTAL REHABILITATION UNDER GENERAL ANESTHESIA: A QUALITATIVE ANALYSIS OF ITS IMPACT ON CHILDREN’S ORAL HEALTH-RELATED QUALITY OF LIFE. - Qazi, Halima Sadia; Amir, Naila; Babar, Palwasha; Alam, Fayyaz; Khan, Asma Munir; Sajjad Ahmad, (Journal of Ayub Medical College Abbottabad, 2025)
Background: Early childhood caries is a widespread condition in the developing world, considerably affecting children’s oral health-related quality of life by causing pain, discomfort, and functional impairments. Dental rehabilitation under general anesthesia is a beneficial intervention for severe early childhood caries, offering substantial relief and marked improvements in oral health-related quality of life. This study explores the impact of dental rehabilitation under general anesthesia on the emotional and social well-being of affected children and their families. Methods: A qualitative study was conducted at the Department of Pediatric Dentistry, Children's Hospital, Pakistan Institute of Medical Sciences, Islamabad. Out of 40 children who underwent comprehensive dental treatment under general anesthesia, the parents of 15 children agreed to participate in focus group discussions and in-depth interviews. Two focal group discussions (with five parents each) and five in-depth interviews were conducted and thematic analysis synthesized data into a comprehensive picture of the participants’ experiences. Results: Before dental rehabilitation under general anesthesia, children experienced pain, sleep issues, behavioral problems, poor academics, and social withdrawal, causing emotional and financial stress for families. After treatment, children showed improved behavior, school performance, and well-being. Parents reported enhanced family dynamics and reduced financial burdens, significantly improving overall quality of life. Conclusion: Dental Rehabilitation treatment under general anesthesia, substantially improves children’s oral and functional health, emotional stability, and social interaction, while positively influencing family well-being. Parents expressed high levels of satisfaction, highlighting it as a valuable intervention for managing extensive forms of early childhood caries and enhancing overall quality of life.